2003
DOI: 10.1089/109065703322783725
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Fragile X in 5,000 Consecutive Newborn Males

Abstract: Fragile X syndrome (FXS) is the commonest cause of inherited mental retardation in males. Even though this affirmation is repeated in virtually all papers referring to FXS, the precise frequency of this syndrome in the general population is unknown. We present a general population screening analyzing an anonymous series of 5,000 consecutive newborn males from the neonatal screening program of the population of Catalonia in Spain. The aim of the study is to determine the incidence of FXS via a simple and econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 28 publications
1
32
1
2
Order By: Relevance
“…In a previous screen for expanded FMR1 alleles using blood spots, Rife et al 31 presented a general population screening of 4937 newborn blood spots from males collected throughout the Catalonia region in Spain. The screening yielded a frequency of 1/2466 full mutation males and 1/1233 premutation carriers.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous screen for expanded FMR1 alleles using blood spots, Rife et al 31 presented a general population screening of 4937 newborn blood spots from males collected throughout the Catalonia region in Spain. The screening yielded a frequency of 1/2466 full mutation males and 1/1233 premutation carriers.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Catalonia we found an incidence of 1:2466 male and 1:8333 females. 1 This difference between males and females is because of the reduced penetrance of FXS in females. It is also important to highlight the high incidence of premutation carriers (55 -200 CGG repeats) in the general population, which has been estimated in 1 of 813 males and 1 of 259 females.…”
Section: Introductionmentioning
confidence: 99%
“…The real incidence of the syndrome is not known, but epidemiological studies indicate that it is responsible for mental retardation in 1 in 4,000-6,000 males and in 1 in 7,000-10,000 females of European descendent (for review Hagerman, 2002). In a study performed in Catalonia it gave an incidence of 1:2,466 male and 1:8,333 females (Rife et al, 2003). It is also important to highlight the high incidence of premutation carriers, 1 in 1,233 males and 1 in 411 females (Rife et al, 2003).…”
Section: Introductionmentioning
confidence: 96%